A Ketrampilan Guru Mengelola Kelas Pada Anak ABK Di SLB Samudra Terra Athena - Dewa, DewayaniAmaliaPramesthi (STILISTIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Abstract: The purpose of this research is to analyse the skills needed by a teacher in managing a class in a SLB. Children with special needs have different and varied learning needs, including in terms of social, cognitive, and emotional skills. Therefore, teachers need to have special skills in managing the classroom in order to create an effective learning environment for all students. In this study the methodology used is a qualitative research methodology with data collection techniques. In this study, researchers conducted interviews with teachers and conducted some documentation in order to collect data. Based on the results of the research that has been done, it can be concluded that the classroom management applied by the teacher at SLB Samudra Terra Athena is good. Both from the arrangement of the facilities and the arrangement of the students. In terms of facility arrangements, teachers at SLB Samudra Terra Athena have made use of the existing facilities. Meanwhile, in the arrangement of students in SLB Samudra Terra Athena, the teacher places more emphasis on grouping students, mentoring and assignments, as well as extracurricular activities. Keywords: teacher skills, class management, children with special needs